2005
DOI: 10.1038/sj.bjc.6602739
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic invasion using D2-40 monoclonal antibody and its relationship to lymph node micrometastasis in pN0 gastric cancer

Abstract: The monoclonal antibody D2-40 is a specific lymphatic endothelial markers and D2-40 staining have been applicable to evaluate lymphatic invasion in various malignant neoplasms. In the present study, we investigated lymph node micrometastasis determined by immunohistochemistry (IHC) and reverse transcription -polymerase chain reaction (RT -PCR) in all dissected lymph nodes obtained from 80 patients with node-negative gastric cancer, and analysed the relationship between micrometastasis and clinicopathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 22 publications
5
82
2
1
Order By: Relevance
“…The gastric cancer cell lines, MKN-7, MKN-45, MKN-74, and NUGC-4, were cultured in RPMI 1640 (Nissui Pharmaceutical Co. Ltd., Tokyo, Japan) supplemented with 10% fetal calf serum (Mitsubishi Kasei, Tokyo, Japan), 100 units ⁄ mL penicillin and 100 units ⁄ mL streptomycin. All cell lines were incubated at 37°C in a humidified atmosphere containing 5% CO 2 , as previously described (27,28) and then examined by immunocytochemistry and RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The gastric cancer cell lines, MKN-7, MKN-45, MKN-74, and NUGC-4, were cultured in RPMI 1640 (Nissui Pharmaceutical Co. Ltd., Tokyo, Japan) supplemented with 10% fetal calf serum (Mitsubishi Kasei, Tokyo, Japan), 100 units ⁄ mL penicillin and 100 units ⁄ mL streptomycin. All cell lines were incubated at 37°C in a humidified atmosphere containing 5% CO 2 , as previously described (27,28) and then examined by immunocytochemistry and RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated and purified using phenol-chloroform as previously described. (27,28) The concentration and purity of the total RNA were determined using a GeneQuant pro UV ⁄ Vis spectrophotometer (Amersham Pharmacia Biotech, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The greatest advantage of the RT‐PCR assay is its high sensitivity for the molecular detection of CTC. We previously investigated its sensitivity using an in vitro model system with serially diluted gastric tumor cells mixed with peripheral blood cells from healthy donors 14. The findings of this cell spiking study showed that the RT‐PCR assay detected 10 tumor cells/107 donor‐derived peripheral blood cells.…”
Section: Detection Of Ctcmentioning
confidence: 99%